Recognition of a High Affinity MHC Class I-Restricted Epitope of Myelin Oligodendrocyte Glycoprotein by CD8+ T Cells Derived from Autoantigen-Deficient Mice - Leech, Melanie D.; Carrillo-Vico, Antonio; Liblau, Roland S.; Anderton, Stephen M. (Frontiers in Immunology, 2011)
CD4+ T cells have a well-defined pathogenic role in experimental autoimmune encephalomyelitis, the rodent model of multiple sclerosis (MS), yet CD8+ T cells are commonly found in MS lesions. To determine whether immunological tolerance might impact differently on CD4+ versus CD8+ T cells, we studied T cell responses in mice genetically deficient for the central nervous system (CNS) autoantigen myelin oligodendrocyte glycoprotein (MOG) versus wild type C57BL/6 mice. We show that MOG-/- mice have enhanced sensitivity to immunization with the immunodominant peptide of MOG(35-55), as evidenced by increased expansion of both CD4+ and CD8+ T cell subsets. Most strikingly, CD8+ T cells from MOG-/- mice responded to a novel T cell epitope which binds to MHC class I with high affinity. Despite this, MOG-responsive CD8+ T cells sourced from either wild type or MOG-/- mice failed to initiate CNS inflammation upon transfer to MOG-sufficient mice. In our hands, this capacity was only found in CD4+ T cells. However, MOG-/- CD4+ cells did not show greater pathogenic activity than their wild type counterparts. Our data indicate that, in the presence of endogenous MOG, CD8+ T cells capable of responding to a MHC class I-restricted epitope that can be stably expressed are subject to rigorous control through central and/or peripheral tolerance.